Model Sole Berbantuan Google Sites Untuk Meningkatkan Kemampuan Siswa Menyelesaikan Masalah Geografi - Riska Br Ginting, Ersa; Sriartha, I Putu; Made Astawa3, Ida Bagus (Universitas Muhammadiyah Surakarta, 2025)
This study aims to: (1) Describe the implementation of the SOLE model assisted by Google Sites in geography learning, and (2) Analyze the effectiveness and impact of the SOLE model assisted by Google Sites on students' problem-solving abilities. The research was conducted at SMA Negeri 1 Seririt with tenth-grade students. The study employed a pretest-posttest nonequivalent control group design. The experimental and control classes were selected using a simple random sampling technique from pairs of equivalent classes based on a prior class equivalence test. Based on this selection, class X-7, consisting of 36 students, was designated as the experimental group, while class X-9, also consisting of 36 students, served as the control group. Data were collected through observations and essay tests using validated instruments. The data were analyzed using descriptive and inferential statistical techniques with a t-test.The findings indicate that: (1) The implementation of the SOLE model assisted by Google Sites in geography learning falls into the high category, with an average score of 87.5, (2) The N-Gain score in the experimental class was 0.70 (moderate category), while the control class scored 0.122 (low category), and (3) The SOLE model assisted by Google Sites had a significant impact on students' problem-solving abilities in geography learning, as evidenced by Sig (2- tailed) = 0.000 < 0.05 at p = 0.05. Based on these results, it is recommended that geography teachers implement the SOLE model assisted by Google Sites to enhance students' problem-solving skills in geography learning.